A fast battery balance method for a modular-reconfigurable battery energy storage system - Huang, Huizhen (2024)
Battery energy storage systems (BESSs) are widely utilized in various applications, e.g. electric vehicles, microgrids, and data centres. However, the structure of multiple cell/module/pack BESSs causes a battery imbalance problem that severely affects BESS reliability, capacity utilization, and battery lifespan. The available balance schemes introduce extra equalizers and suffer from slow balance speed due to the equalizer limits. To tackle this issue, a modular reconfigurable BESS (MR-BESS) topology is introduced in this paper, for which a fast battery balance method is proposed. This combination provides reconfiguration flexibility and fault tolerance capability without the need for any extra components, such as equalizers. Experimental results were performed on a scale-down prototype to verify the operation of the proposed reconfigurable BESS topology and the effectiveness of the fast battery balance method.